Molecular Biomarkers for Prediction of Neurological Outcome after Sudden Circulatory Arrest (Review) - A. M. Golubev; A. N. Kuzovlev; V. V. Antonova; V. E. Zakharchenko; M. V. Petrova; A. V. Grechko (Общая реаниматология, 2018)
The purpose of this review of the 81 publications is to discuss the current national and international data on the prediction of neurological outcomes after sudden circulatory arrest (SCA) using molecular biomarkers. The review discusses the current state of the problem of neurological outcomes after a sudden circulatory arrest, the principal therapeutic measures to improve these outcomes and currently available clinical, laboratory, and instrumental methods of diagnosis and prediction of neurological outcomes after a sudden circulatory arrest.